STRATEGI DIFUSI INOVASI PUSKESMAS PURWOKERTO UTARA 2 DALAM DISEMINASI PROGRAM ANTENATAL CARE TERPADU - Rizki Ardhi Rahma; Prita Suci Nurcandrani; Pundra Rengga Andhita (Jurnal Ilmu Komunikasi PROGRESSIO, 2023)
Purwokerto Utara 2 Health Center is carrying out audiovisual innovations by using Instagram and TikTok as a means of disseminating integrated antenatal care checks with the aim of reducing stunting rates and supporting a demographic bonus in 2045. What time is needed and what is the social system like. This research is based on the theory of Everett M. Rogers which discusses innovation, communication channels, time, social systems, sociotechnology models, health communication, and new media. Therefore used descriptive qualitative analysis with observation, interviews, and documentation. The results show that the innovations carried out by Puskesmas 2 Purwokerto Utara are going well. Acceptance of the innovation took 3 months, but further efforts are still needed. Of the 7 selected informants, 6 accepted and 1 rejected the innovation because of the social norms they adhered to.